CSaaS - a multi-cloud framework for secure file storage technology using open ZFS. (2016) - Jogdand, R.M.; Batlad, S.B.; Gangodkar, Durgaprasad
Many business enterprises are migrating towards multi-cloud to store the enterprise data. Multi-cloud approach overcomes various limitations faced by single cloud environment. The advantages include freedom from vendor-lock-in, and improved availability and security of the data. File storage approach supported by network attached storage (NAS) proves to be a better solution especially for structured database storage that needs to handle random read/write loads and virtual machine file system. In this paper, we propose a novel framework that helps the enterprises to store their data in the multi-cloud environment using file storage technology. This framework, referred to as controller for storage as a service (CSaaS), comprises four modules which facilitates the clients to achieve secure data storage on multiple clouds. Performance evaluation for average data transfer rate and completion latency show that read and rand-read performance of CSaaS has been significantly improved as compared to single CSP, for file sizes up to 90 MB.